Optimal multi-writer multi-reader atomic register - Israeli, Amos; Shaham, Amnon (1992)
Abstract: "This paper addresses the wide gap in space complexity of atomic, multi-writer, multi-reader register implementations. While the space complexity of all previous implementations is linear, the lower bounds are logarithmic. We present two implementations which close this gap: The first implementation uses multi-reader physical registers while the second uses single-reader physical registers. Both implementations are optimal with respect to the two most important complexity criteria: Their space complexity is logarithmic and their time complexity is linear."
Keywords: Multiprocessors; Registers (Computers)